American Community Survey (ACS): Public Use Microdata Sample (PUMS), 2000 ([Verlag nicht ermittelbar], 2005)
The American Community Survey (ACS) is a nationwide survey designed to provide communities a fresh look at how they are changing. It will replace the decennial long form in future censuses and is a critical element in the Bureau of the Census re-engineered 2010 census. The American Community Survey is conducted under the authority of Title 13, United States Code, Sections 141 and 193, and response is mandatory.